Teacher relations - Teaching aids and school efficiency in Uganda : Case of Kabale Municipality - Kansiime, Gilbert A.; Rugyendo, Medard; Karukwitsya, Diane K. (Journal of African Interdisciplinary Studies, 2017)
The study was done on Teacher relations-Teaching Aids and school efficiency in Uganda: Case of Kabale Municipality. The emphasize was put on Teacher Relations–teaching aids and linkage to School efficiency and performance in primary and secondary schools (Kigezi High School Primary and Kabale Primary School, Kabale Secondary School and Kabale Trinity College). Objectives of the study include: 1) To evaluate the teacher relations and expectations with other stakeholders in the Primary and secondary Educational Institutions in Kabale Municipality; and 2) Examine the factors promote the use of Teaching aids/tools in Primary and secondary schools in Kabale Municipality; 3) To suggest recommendations to improve teacher relations and the use of Teaching aids/tools in improving performance in Primary and secondary schools in Kabale Municipality. The research methodology that was used included; the total study population was 70 respondents and these included teachers (20), school administrators (8), students/pupils (20), parents (20), and 2 officials from Inspectorate of Education and sports–Kabale Municipality. The respondents were selected randomly and purposively. Data was collected using questionnaires (administered to teachers, school administrators and pupils) while the parents and officials from Inspectorate of Education and sports–Kabale Municipality were interviewed. Data was analysed and a report compiled. The identified Teacher Relations linkage with school efficiency and performance framework in Primary and secondary schools in Kabale Municipality include; Teacher-teacher relations, Teacher student/Pupil relations, Teacher–School administrator relations, Teacher–School Foundation body relations, Teacher-Community relations, Teacher-Parents relations, Teacher and teachers’ associations (trade unions) and Teacher and Government relations.